Modified nanofiber material as well as preparation method and application thereof

By combining modified nanocellulose with temperature-responsive monomer and initiator, modified nanofiber materials with magnetic and temperature response are prepared, which solves the problems of adsorbent material recycling and secondary pollution problems, and achieves low cost and high efficiency wastewater treatment.

CN119386824AActive Publication Date: 2025-02-07INST OF BIOLOGICAL & MEDICAL ENG GUANGDONG ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411636302.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-07
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

Existing adsorbent materials are difficult to recycle after wastewater treatment, and the regeneration process may cause secondary pollution, increasing treatment costs.

Method used

The nanocellulose is modified with copper-manganese-iron composite magnetic additives and combined with temperature-responsive monomers and initiators to prepare modified nanofiber materials with magnetic and temperature double responses. The material is separated by a magnetic field and elution of pollutants and regeneration of materials through temperature control.

Benefits of technology

It realizes low-cost recycling and regeneration of adsorbent materials, avoids secondary pollution, and improves the efficiency and economicality of wastewater treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119386824A_ABST
    Figure CN119386824A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of adsorption materials, and particularly relates to a modified nanofiber material as well as a preparation method and application thereof. The modified nanofiber material is prepared from the following raw materials: modified nanocellulose, a temperature response monomer and an initiator, the modified nano-crystalline cellulose is obtained by modifying nano-crystalline cellulose by adopting a copper-manganese-iron composite network magnetic additive. The specific copper-manganese-iron composite magnetic additive is adopted to modify the nano-cellulose to obtain the modified nano-cellulose, and under the action of the initiator, the modified nano-cellulose and the temperature response monomer act together, so that the modified nano-fiber material has good adsorption performance and magnetic and temperature double response, and the magnetic and temperature response performance is improved. In the separation process, separation can be achieved through a magnetic field, meanwhile, adsorbed target pollutants can be eluted by changing the temperature, low-cost recovery and regeneration of the adsorbent are achieved, and the problems that a traditional water treatment adsorbent is difficult to recover after being used and secondary pollution is caused by adsorbent regeneration are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adsorption materials, and particularly relates to a modified nanofiber material and a preparation method and application thereof. Background Art

[0002] With the rapid development of industry and agriculture, a large amount of wastewater and waste gas are discharged, causing certain harm to the atmospheric environment and water environment. Water pollution has become an important issue and problem that needs to be solved urgently.

[0003] At present, in the field of wastewater treatment, wastewater treatment is mainly carried out by adding adsorbent materials, such as activated carbon, zeolite and other biodegradable materials. However, after these adsorbent materials are added to the wastewater for adsorption for a certain period of time, filtration or centrifugation is generally required to separate the adsorbent materials from the pollutants in the wastewater, thereby realizing the recovery of the adsorbent materials. However, this method still has the problem of incomplete separation, which in turn causes secondary pollution and difficulty in recovering the adsorbent materials, and further treatment is required to achieve better separation, which correspondingly increases the additional processing cost. In addition, there is currently a technology for using hydrogels for wastewater treatment, but the adsorption performance is difficult to meet the use requirements, the adsorption performance needs to be further improved, and after adsorption, it is necessary to soak in an acidic solution to elute the adsorbed pollutants. The use of an acidic solution not only increases the process flow and the post-processing cost, but also causes pollution to a certain extent.

[0004] Therefore, it is of great significance to provide an adsorption material with good adsorption performance, which can be recycled and regenerated at low cost and will not cause secondary pollution. Summary of the invention

[0005] The present invention aims to solve one or more technical problems existing in the above-mentioned prior art, and at least provide a beneficial choice or create conditions. Specifically, the present invention provides a modified nanofiber material, which has good adsorption performance, can realize low-cost recovery and regeneration of adsorbent materials, and will not cause secondary pollution; it solves the problem that traditional water treatment adsorbents are difficult to recover after use and the problem of secondary pollution caused by adsorbent regeneration.

[0006] The inventive concept of the present invention: the raw materials for preparing the modified nanofiber material of the present invention include modified nanocellulose, temperature-responsive monomers, and initiators; the modified nanocellulose is obtained by modifying nanocellulose with a copper-manganese-iron composite magnetic auxiliary agent. The present invention obtains modified nanocellulose by using a specific copper-manganese-iron composite magnetic auxiliary agent to modify nanocellulose, and under the action of the initiator, the modified nanocellulose and the temperature-responsive monomer work together to make the modified nanofiber material have both magnetic and temperature responses and good adsorption performance; during separation, the magnetic modified nanofiber material can be separated by a magnetic field, and the adsorbed target pollutants can be eluted by changing the temperature, thereby realizing low-cost recovery and regeneration of the adsorbent-modified nanofiber material, which can solve the problem of difficult recovery of traditional water treatment adsorbents after use and the problem of secondary pollution caused by adsorbent regeneration.

[0007] Therefore, a first aspect of the present invention provides a modified nanofiber material.

[0008] Specifically, the modified nanofiber material is prepared from raw materials including modified nanocellulose, temperature-responsive monomers, and initiators;

[0009] The modified nanocellulose is obtained by modifying the nanocellulose with a copper-manganese-iron composite magnetic auxiliary agent.

[0010] Preferably, the copper-manganese-iron composite magnetic additive includes cupric chloride, manganese chloride and ferric chloride; the molar ratio of ferric chloride to cupric chloride and manganese chloride is (0.5-1.5):(0.5-1.5):1.

[0011] Further preferably, the copper-manganese-iron composite network magnetic additive includes cupric chloride, manganese chloride and ferric chloride; the molar ratio of ferric chloride to cupric chloride and manganese chloride is (0.8-1.2):(0.8-1.2):1.

[0012] More preferably, the copper-manganese-iron composite network magnetic additive includes cupric chloride, manganese chloride and ferric chloride; the molar ratio of ferric chloride to cupric chloride and manganese chloride is 1:1:1.

[0013] Preferably, the copper-manganese-iron composite magnetic additive includes FeCl 3 6H 2 O, CuCl 2 ·2H 2 O and MnCl 2 ·4H 2 O.

[0014] Specifically, the present invention adopts a copper-manganese-iron composite magnetic additive compounded with specific types of copper chloride, manganese chloride and ferric chloride. Iron-manganese and manganese-copper can generate layered structures through hydrothermal reaction. When the three additives of copper chloride, manganese chloride and ferric chloride exist at the same time, the formation of a monoclinic-tetragonal phase interface with a large number of defects inhibits the growth of nanoparticles, which is conducive to maintaining a smaller crystal size and a higher surface area, and finally generates a complex three-dimensional network morphology with excellent adsorption performance. That is, the copper-manganese-iron composite magnetic additive is used to modify nanocellulose, which can not only give the material magnetic response ability, but also enhance the adsorption performance of the modified nanofiber material.

[0015] Preferably, the diameter of the nanocellulose is 1-110 nm; further preferably, the diameter of the nanocellulose is 1-100 nm.

[0016] Preferably, the nanocellulose is a nanofiber prepared by a mechanical method or an acid hydrolysis method using fiber raw materials from nature, including at least one of cellulose nanocrystals (CNC) and nanocellulose (CNF).

[0017] Specifically, CNF is obtained by a mechanical method, and CNC is obtained by an acid hydrolysis method.

[0018] Preferably, the mass ratio of the modified nanocellulose and the temperature-responsive monomer is (0.8-12):1; further preferably, the mass ratio of the modified nanocellulose and the temperature-responsive monomer is (0.9-11):1; further preferably, the mass ratio of the modified nanocellulose and the temperature-responsive monomer is (1-10):1.

[0019] Preferably, the mass ratio of the initiator to the temperature-responsive monomer is 1:(40-120); further preferably, the mass ratio of the initiator to the temperature-responsive monomer is 1:(45-110); further preferably, the mass ratio of the initiator to the temperature-responsive monomer is 1:(50-100).

[0020] Preferably, the temperature responsive monomer includes at least one of N-isopropylacrylamide (NIPAM), polyoxyethylene ether (PEO), and polyvinylpyrrolidone (PVP).

[0021] Preferably, the initiator includes at least one of potassium persulfate, ammonium persulfate and sodium persulfate.

[0022] The second aspect of the present invention provides a method for preparing the modified nanofiber material according to the first aspect of the present invention.

[0023] Specifically, the method for preparing the modified nanofiber material comprises the following steps:

[0024] The raw material components are mixed and reacted to obtain the modified nanofiber material.

[0025] Preferably, the reaction temperature is 55-85°C; the reaction time is 0.5-2.2h; further preferably, the reaction temperature is 60-80°C; the reaction time is 0.5-2h.

[0026] Preferably, the method for preparing the modified nanofiber material comprises the following steps:

[0027] The modified nanocellulose is mixed with a temperature-responsive monomer, stirred at a constant temperature, and then an initiator is added to react to obtain the modified nanofiber material.

[0028] Preferably, the modified nanofiber material is separated by a magnet and washed for later use.

[0029] Preferably, constant temperature stirring is maintained during the reaction.

[0030] Preferably, the method for preparing the modified nanocellulose comprises the following steps:

[0031] The nanocellulose, copper-manganese-iron composite magnetic auxiliary agent and water are mixed, the pH is adjusted to alkaline, and the mixture is reacted to obtain the modified nanocellulose.

[0032] Preferably, the pH is adjusted to alkaline using a pH adjuster.

[0033] Specifically, the modified nanocellulose is prepared by hydrothermal reaction of nanocellulose, copper-manganese-iron composite network magnetic auxiliary agent and pH regulator. Compared with the solid phase reaction to prepare the modified nanocellulose, the hydrothermal reaction used in the present invention has a higher reaction rate and lower equipment requirements, and compared with the organic phase reaction to prepare the modified nanocellulose, the present invention is environmentally friendly and has no secondary pollution.

[0034] Specifically, the amount of water added is just enough to disperse the nanocellulose, and the solid content of the nanocellulose is controlled to be less than 5%.

[0035] Preferably, the pH adjuster comprises aqueous ammonia.

[0036] Preferably, the mass concentration of the ammonia water is 20-30%; further preferably, the mass concentration of the ammonia water is 22-27%; further preferably, the mass concentration of the ammonia water is 25%.

[0037] Preferably, the reaction temperature is 150-250°C, the reaction time is 0.5-2.2h, and the reaction pH is 8-11; further preferably, the reaction temperature is 180-220°C, the reaction time is 0.5-2h, and the reaction pH is 9-10.

[0038] The third aspect of the present invention provides a use of the modified nanofiber material described in the first aspect of the present invention in wastewater or waste gas treatment.

[0039] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:

[0040] (1) The raw materials for preparing the modified nanofiber material of the present invention include modified nanocellulose, a temperature-responsive monomer, and an initiator; the modified nanocellulose is obtained by modifying nanocellulose with a copper-manganese-iron composite magnetic auxiliary agent. The present invention uses a specific copper-manganese-iron composite magnetic auxiliary agent to modify nanocellulose to obtain modified nanocellulose, and under the action of the initiator, the modified nanocellulose and the temperature-responsive monomer work together to make the modified nanofiber material have good adsorption performance and dual magnetic and temperature responses. During separation, the magnetic modified nanofiber material can be separated by a magnetic field, and the adsorbed target pollutants can be eluted by changing the temperature, thereby realizing low-cost recovery and regeneration of the adsorbent, which can solve the problem that traditional water treatment adsorbents are difficult to recover after use and the problem of secondary pollution caused by adsorbent regeneration.

[0041] (2) The preparation process of the present invention is simple and convenient for large-scale production and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is a scanning electron microscope image of the modified nanofiber material prepared in Example 1 of the present invention;

[0043] Figure 2 This is a Fourier infrared spectrum of the modified nanofiber material prepared in Example 1 of the present invention;

[0044] Figure 3 This is a graph showing the atomic force microscope test results of the nanocellulose and modified nanofiber materials of Example 1 of the present invention;

[0045] Figure 4 This is an adsorption curve diagram of methylene blue and copper ions by the modified nanofiber material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0046] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.

[0047] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.

[0048] The raw material components and amounts (g) of Examples 1-6 of the present invention and Comparative Examples 1-6 are shown in Table 1.

[0049] Table 1: Raw material components and dosages (g) of Examples 1-6 and Comparative Examples 1-6

[0050]

[0051] In Table 1, “-” means no addition.

[0052] Example 1

[0053] A modified nanofiber material, the preparation raw materials of which include modified nanocellulose, N-isopropylacrylamide, and an initiator; the amount of each component is shown in Table 1.

[0054] A method for preparing a modified nanofiber material comprises the following steps:

[0055] (1) adding modified nanocellulose and N-isopropylacrylamide into a reaction vessel, setting the temperature to 70° C. and maintaining constant temperature stirring, then adding an initiator and maintaining constant temperature stirring;

[0056] (2) The reaction time is set to 1 hour. After the reaction, the product is separated and taken out with a magnet and washed for later use to obtain a hydrogel, which is the modified nanofiber material.

[0057] The method for preparing modified nanocellulose comprises the following steps:

[0058] Add nanocellulose (CNF) into the reaction vessel and keep stirring at constant temperature, then add FeCl 3 6H 2 O,CuCl 2 ·2H 2 O and MnCl 2 ·4H 2 O, mix well; then add ammonia water with a mass concentration of 25%, adjust the pH value of the solution to 9, continue to stir well and add it into the high-pressure reactor, set the temperature to 200°C and react for 2h. The modified nanocellulose is separated with a magnet and washed for later use.

[0059] The modified nanofiber material prepared in Example 1 was observed by scanning electron microscopy. Figure 1 As shown by Figure 1It can be seen that the nanocellulose presents a honeycomb porous structure after modification, and the magnetic particles modified by magnetism are evenly distributed in the pore structure.

[0060] The modified nanofiber material prepared in Example 1 was subjected to Fourier infrared spectroscopy test (FTIR test). The FTIR graph is as follows: Figure 2 shown.

[0061] The nanocellulose of Example 1 and the modified nanofiber material of Example 1 were subjected to atomic force microscopy test (AFM test). The AFM test results are as follows: Figure 3 As shown, Figure 3 Figure (a) is the AFM test result of nanocellulose in Example 1. Figure 3 Figure (b) is the AFM test result of the modified nanofiber material in Example 1; deg represents the depth of the position in the figure.

[0062] from Figure 2 It can be seen that 3340cm -1 、2898cm -1 and 1621cm -1 The peaks at 1636 cm (corresponding to the stretching vibration of OH bond, the stretching vibration of CH bond and the bending of OH) are the peaks of the matrix material nanocellulose; -1 and 1556cm -1 The peaks at 1378 cm-1 come from the poly(N-isopropylacrylamide) (PNIPAM) chain, corresponding to the NH stretching and C=O stretching of amide I, respectively; -1 The peak at PNIPAM(-CH(CH 3 ) 2 ) groups are produced; the above results indicate that the modified nanofiber material with magnetic-temperature dual response is successfully prepared.

[0063] from Figure 3 It can be seen that the nanocellulose has a linear and uniformly dispersed microstructure before modification, but after magnetic modification and temperature-responsive modification, it presents a porous structure, and the magnetic particles are uniformly dispersed in the modified nanocellulose.

[0064] Example 2

[0065] A modified nanofiber material, the preparation raw materials of which include modified nanocellulose, N-isopropylacrylamide, and an initiator; the amount of each component is shown in Table 1.

[0066] A method for preparing a modified nanofiber material comprises the following steps:

[0067] (1) adding modified nanocellulose and N-isopropylacrylamide into a reaction vessel, setting the temperature to 70° C. and maintaining constant temperature stirring, then adding an initiator and maintaining constant temperature stirring;

[0068] (2) The reaction time is set to 1 hour. After the reaction, the product is separated and taken out with a magnet and washed for later use to obtain a hydrogel, which is the modified nanofiber material.

[0069] The method for preparing modified nanocellulose comprises the following steps:

[0070] Add nanocellulose (CNF) into the reaction vessel and keep stirring at constant temperature, then add FeCl 3 6H 2 O,CuCl 2 ·2H 2 O and MnCl 2 ·4H 2 O, mix well; then add ammonia water with a mass concentration of 25%, adjust the pH value of the solution to 9, continue to stir well and add it into the high-pressure reactor, set the temperature to 250°C and react for 2h. The modified nanocellulose is separated with a magnet and washed for use.

[0071] Example 3

[0072] A modified nanofiber material, the preparation raw materials of which include modified nanocellulose, N-isopropylacrylamide, and an initiator; the amount of each component is shown in Table 1.

[0073] A method for preparing a modified nanofiber material comprises the following steps:

[0074] (1) adding modified nanocellulose and N-isopropylacrylamide into a reaction vessel, setting the temperature to 65° C. and maintaining constant temperature stirring, then adding an initiator and maintaining constant temperature stirring;

[0075] (2) The reaction time is set to 0.5 h. After the reaction, the product is separated and taken out with a magnet and washed for later use to obtain a hydrogel, which is the modified nanofiber material.

[0076] The method for preparing modified nanocellulose comprises the following steps:

[0077] Add nanocellulose (CNF) into the reaction vessel and keep stirring at constant temperature, then add FeCl 3 6H 2 O,CuCl 2 ·2H 2 O and MnCl 2 ·4H 2O, mix well; then add ammonia water with a mass concentration of 25%, adjust the pH value of the solution to 9, continue to stir well and add it into the high-pressure reactor, set the temperature to 200°C and react for 2h. The modified nanocellulose is separated with a magnet and washed for later use.

[0078] Example 4

[0079] A modified nanofiber material, the preparation raw materials of which include modified nanocellulose, polyoxyethylene ether, and an initiator; the amount of each component is shown in Table 1.

[0080] A method for preparing a modified nanofiber material comprises the following steps:

[0081] (1) adding modified nanocellulose and polyoxyethylene ether into a reaction vessel, setting the temperature to 70° C. and maintaining constant temperature stirring, then adding an initiator and maintaining constant temperature stirring;

[0082] (2) The reaction time is set to 1 hour. After the reaction, the product is separated and taken out with a magnet and washed for later use to obtain a hydrogel, which is the modified nanofiber material.

[0083] The method for preparing modified nanocellulose comprises the following steps:

[0084] Add nanocellulose (CNF) into the reaction vessel and keep stirring at constant temperature, then add FeCl 3 6H 2 O,CuCl 2 ·2H 2 O and MnCl 2 ·4H 2 O, mix well; then add ammonia water with a mass concentration of 25%, adjust the pH value of the solution to 9, continue to stir well and add it into the high-pressure reactor, set the temperature to 200°C and react for 2h. The modified nanocellulose is separated with a magnet and washed for later use.

[0085] Example 5

[0086] A modified nanofiber material, the preparation raw materials of which include modified nanocellulose, polyvinyl pyrrolidone, and an initiator; the amount of each component is shown in Table 1.

[0087] A method for preparing a modified nanofiber material comprises the following steps:

[0088] (1) adding modified nanocellulose and polyvinyl pyrrolidone into a reaction vessel, setting the temperature to 70° C. and maintaining constant temperature stirring, then adding an initiator and maintaining constant temperature stirring;

[0089] (2) The reaction time is set to 1 hour. After the reaction, the product is separated and taken out with a magnet and washed for later use to obtain a hydrogel, which is the modified nanofiber material.

[0090] The method for preparing modified nanocellulose comprises the following steps:

[0091] Add nanocellulose (CNF) into the reaction vessel and keep stirring at constant temperature, then add FeCl 3 6H 2 O,CuCl 2 ·2H 2 O and MnCl 2 ·4H 2 O, mix well; then add ammonia water with a mass concentration of 25%, adjust the pH value of the solution to 10, continue to stir well and add it into the high-pressure reactor, set the temperature to 200°C and react for 2h. The modified nanocellulose is separated by a magnet and washed for use.

[0092] Example 6

[0093] A modified nanofiber material, the preparation raw materials of which include modified nanocellulose, polyvinyl pyrrolidone, and an initiator; the amount of each component is shown in Table 1.

[0094] A method for preparing a modified nanofiber material comprises the following steps:

[0095] (1) adding modified nanocellulose and polyvinyl pyrrolidone into a reaction vessel, setting the temperature to 70° C. and maintaining constant temperature stirring, then adding an initiator and maintaining constant temperature stirring;

[0096] (2) The reaction time is set to 1 h. After the reaction, the product is separated and taken out with a magnet and washed for later use to obtain a hydrogel, which is a magnetically modified nanofiber material.

[0097] The method for preparing modified nanocellulose comprises the following steps:

[0098] Add nanocellulose (CNF) into the reaction vessel and keep stirring at constant temperature, then add FeCl 3 6H 2 O,CuCl 2 ·2H 2 O and MnCl 2 ·4H 2 O, mix well; then add ammonia water with a mass concentration of 25%, adjust the pH value of the solution to 9, continue to stir well and add it into the high-pressure reactor, set the temperature to 200°C and react for 2h. The modified nanocellulose is separated with a magnet and washed for later use.

[0099] Comparative Example 1

[0100] The only difference between Comparative Example 1 and Example 2 is that Comparative Example 1 does not use the copper-manganese-iron composite network magnetic additive to modify the nanocellulose, that is, an equal amount of nanocellulose is used to replace the modified nanocellulose in Example 1, and the rest is the same as Example 2.

[0101] Specifically, the preparation method of the modified nanofiber material in Comparative Example 1 comprises the following steps:

[0102] (1) adding nanocellulose and N-isopropylacrylamide into a reaction vessel, setting the temperature to 70° C. and maintaining constant temperature stirring, then adding an initiator and maintaining constant temperature stirring;

[0103] (2) The reaction time is set to 1 h. After the reaction, the product is separated by filtering with filter paper and washed for later use to obtain a hydrogel, i.e., a modified nanofiber material.

[0104] Comparative Example 2

[0105] The difference between Comparative Example 2 and Example 2 is that the raw material for preparing the modified nanofiber material in Comparative Example 2 only contains modified nanocellulose, and does not contain an initiator and a temperature-responsive monomer.

[0106] The preparation method of modified nanocellulose in Comparative Example 2 is the same as that in Example 2.

[0107] Comparative Example 3

[0108] The difference between Comparative Example 3 and Example 3 is that Comparative Example 3 changes the reaction temperature in the preparation process of the modified nanofiber material, and the rest is the same as Example 3.

[0109] Specifically, the preparation method of the modified nanofiber material in Comparative Example 3 comprises the following steps:

[0110] (1) adding modified nanocellulose and N-isopropylacrylamide into a reaction vessel, setting the temperature to 50° C. and maintaining constant temperature stirring, then adding an initiator and maintaining constant temperature stirring;

[0111] (2) The reaction time is set to 0.5 h. After the reaction, the product is separated and taken out with a magnet and washed for later use to obtain a hydrogel, which is the modified nanofiber material.

[0112] The method for preparing modified nanocellulose comprises the following steps:

[0113] Add nanocellulose (CNF) into the reaction vessel and keep stirring at constant temperature, then add FeCl 3 6H 2 O,CuCl 2 ·2H 2 O and MnCl 2 ·4H 2O, mix well; then add ammonia water with a mass concentration of 25%, adjust the pH value of the solution to 9, continue to stir well and add it into the high-pressure reactor, set the temperature to 200°C and react for 2h. The modified nanocellulose is separated with a magnet and washed for later use.

[0114] Comparative Example 4

[0115] The difference between Comparative Example 4 and Example 1 is that Comparative Example 4 uses an equal amount of MnCl 2 ·4H 2 O replaces CuCl 2 ·2H 2 O, i.e. without CuCl 2 ·2H 2 O, the rest is the same as in Example 1.

[0116] The preparation method of the modified nanofiber material and modified nanocellulose in Comparative Example 4 is the same as that in Example 1.

[0117] Comparative Example 5

[0118] The difference between Comparative Example 5 and Example 1 is that Comparative Example 5 uses an equal amount of CuCl 2 ·2H 2 O replaces MnCl 2 ·4H 2 O, i.e. without MnCl 2 ·4H 2 O, the rest is the same as in Example 1.

[0119] The preparation method of the modified nanofiber material and modified nanocellulose in Comparative Example 5 is the same as that in Example 1.

[0120] Comparative Example 6

[0121] The difference between Comparative Example 6 and Example 1 is that Comparative Example 6 uses an equal amount of CuCl 2 ·2H 2 O replaces FeCl 3 6H 2 O, i.e. without FeCl 3 6H 2 O, the rest is the same as in Example 1.

[0122] The preparation method of the modified nanofiber material and modified nanocellulose in Comparative Example 6 is the same as that in Example 1.

[0123] Performance Testing

[0124] 1. Adsorption performance and response performance test

[0125] The adsorption performance and response performance of the modified nanofiber materials prepared in Examples 1-6 and Comparative Examples 1-6 were tested, and the test method was as follows:

[0126] Adsorption performance test: The adsorption performance of the modified nanofiber materials prepared in Examples 1-6 and Comparative Examples 1-6 was tested using the dye methylene blue (MB) as an indicator. First, a dye mother solution with a concentration of 1000 mg / L was prepared, and then diluted to 20 mg / L to obtain a test solution (dye solution). During the test, at 25°C, 10 mg of the modified nanofiber materials prepared in Examples 1-6 and Comparative Examples 1-6 were added to 10 mL of a dye solution with a concentration of 20 mg / L to obtain a mixture. The mixture was then placed on a TS110X30 vibrating screen and tested at a stirring speed of 150 rpm. After a predetermined time (1 h), the dye concentration was tested using an ultraviolet spectrophotometer. According to the test results, the dye saturated adsorption capacity (Qe, mg / g modified nanofiber material) can be obtained.

[0127] Response performance test: 10 mg of each modified nanofiber material prepared in Examples 1-6 and Comparative Examples 1-6 were added to 10 mL of a 20 mg / L (initial concentration C 0 ) in a dye solution (the dye solution is the same as the adsorption performance test) to obtain a mixture, the mixture is placed on the above-mentioned TS110X30 vibrating screen at a temperature of 25°C and maintained for 2 hours to reach equilibrium, and the concentration of the dye is tested using an ultraviolet spectrophotometer and recorded as C 1 , and then calculate the dye removal efficiency R according to the initial concentration 1 %(R 1 % = (C 0 -C 1 ) / C 0 × 100%); the temperature was fixed at 37°C and maintained for another 2 hours to reach equilibrium, and the concentration of the dye was tested using an ultraviolet spectrophotometer and recorded as C 2 , calculate the dye removal efficiency R 2 %(R 2 % = (C 0 -C 2 ) / C 0 × 100%), and then the temperature was fixed at 25°C and maintained for another 2 hours to reach equilibrium, and the concentration of the dye was measured using an ultraviolet spectrophotometer and recorded as C 3 , calculate the dye removal efficiency R 3 %(R 3 % = (C 0 -C 3 ) / C 0 ×100%).

[0128] The performance test results of the modified nanofiber materials prepared in Examples 1-6 and Comparative Examples 1-6 are shown in Table 2.

[0129] Table 2: Performance test results of modified nanofiber materials prepared in Examples 1-6 and Comparative Examples 1-6

[0130]

[0131]

[0132] It can be seen from Table 2 that the modified nanofiber material of the present invention has good adsorption performance, and when the temperature rises to 37°C, the removal rate of the dye by the modified nanofiber material decreases, and when the temperature drops back to 25°C, the removal rate of the dye by the modified nanofiber material is significantly improved, indicating that the modified nanofiber material of the present invention has good response performance to temperature.

[0133] It can be seen from Example 1, Example 4 and Example 5 that the effect of changing the type of temperature-responsive monomer on adsorption performance and responsiveness is not much different, but N-isopropyl acrylamide has the best adsorption performance when used as a temperature-responsive monomer. It can be seen from Example 1 and Example 2 that increasing the proportion of temperature-responsive monomers during the reaction can increase the temperature response characteristics of the modified nanofiber material, and at the same time, magnetic modification causes more Fe-OH bonds to exist in the structure of the modified nanofiber material, further increasing its dye adsorption performance. It can be seen from Example 2 and Example 3 that increasing the amount of initiator within a certain range can improve the performance of the modified nanofiber material.

[0134] In Comparative Example 1, nanocellulose was not modified, so the dye adsorption performance of the modified nanofiber material in Comparative Example 1 was worse than that in Example 2, indicating that magnetic modification can not only give the modified nanofiber material magnetic response ability, but also enhance the ability of the modified nanofiber material to adsorb dyes.

[0135] In Comparative Example 2, no temperature-responsive monomer is added, so that when the temperature changes, the removal rate of the dye by the modified nanofiber material does not change significantly, indicating that the modified nanofiber material in Comparative Example 2 has no temperature-responsive behavior in dye adsorption.

[0136] Comparative Example 3 changes the reaction temperature during the preparation of the modified nanofiber material, so that the modified nanofiber material in Comparative Example 3 not only has no temperature responsiveness but also has poor adsorption capacity, which indicates that the preparation process of the modified nanofiber material needs to be carried out under specific conditions.

[0137] From Comparative Examples 4, 5 and 6, it can be seen that the lack of CuCl 2 ·2H 2 O, FeCl 3 6H 2 O、MnCl 2 ·4H 2Any one of O will reduce the adsorption performance of the modified nanofiber material, indicating that the formation of the copper-manganese-iron composite network is the guarantee for the modified nanofiber material to have excellent adsorption performance, and none of the three is dispensable.

[0138] In addition, the present invention also studies the effects of modified nanofiber materials of Example 1, Example 2, and Comparative Examples 1-6 on MB and Cu 2+ The maximum adsorption capacity of MB solution and Cu solution were tested. Specifically, 500 mg / L MB solution and 2+ The solution was used as the mother liquor, and 1 g of the modified nanofiber material of Example 1, Example 2, and Comparative Examples 1-6 was added to 10 mL of the mother liquor at 25° C. to obtain a mixture, and then the mixture was placed on a TS110X30 vibrating screen and tested at a stirring speed of 150 rpm; after a predetermined time (2 h), MB and Cu were tested using an ultraviolet spectrophotometer and an inductively coupled plasma mass spectrometer (ICP-MS). 2+ The concentration of MB and Cu in each group of modified nanofiber materials was calculated. 2+ The actual maximum adsorption capacity of the modified nanofiber material for MB and Cu is shown in Table 3. 2+ The adsorption curve of Figure 4 shown.

[0139] Table 3: Effect of modified nanofiber materials of Example 1, Example 2, Comparative Examples 1-6 on MB and Cu 2+ The maximum adsorption capacity

[0140]

[0141] It can be seen from Table 3 that the modified nanofiber material of the present invention has a significant effect on the performance of MB and Cu 2+ All of them have high maximum adsorption capacity, indicating that their adsorption performance is good.

[0142] Comparative Example 1 did not modify the nanocellulose, so that the modified nanofiber material of Comparative Example 1 had no significant effect on MB and Cu 2+ The maximum adsorption capacity of the modified nanofiber material is significantly lower than that of Example 2, indicating that the magnetic modification gives the modified nanofiber material a stable three-dimensional network structure, which not only gives the modified nanofiber material magnetic responsiveness, but also enhances the ability of the modified nanofiber material to adsorb dyes. 2+ The maximum adsorption capacity of the modified nanofiber material is significantly lower than that of Example 2. Comparative Example 3 changes the reaction temperature during the preparation of the modified nanofiber material, so that the modified nanofiber material of Comparative Example 3 has a high adsorption capacity for MB and Cu. 2+ The maximum adsorption capacity is low. Compared with Example 1, Comparative Examples 4-6 lack CuCl 2 ·2H2 O, FeCl 3 6H 2 O、MnCl 2 ·4H 2 O, that is, no copper-manganese-iron composite network is formed, and its adsorption effect is worse than that of Example 1, which shows that only by using copper chloride, manganese chloride and ferric chloride to modify nanocellulose to form a copper-manganese-iron composite network and the modified nanocellulose and the temperature-responsive monomer work together and are prepared at a certain reaction temperature, can the modified nanofiber material have a higher adsorption capacity and achieve effective adsorption of pollutants.

[0143] 2. Cycle performance test

[0144] The modified nanofiber materials in Example 1 and Comparative Example 4 were regenerated and used again for MB and Cu after the elution step (adding the adsorbed modified nanofiber materials to 100 mL of 0.01 mol / L dilute hydrochloric acid, raising the temperature to 37° C., and eluting at a stirring speed of 150 rpm. After a predetermined time (2 h), the modified nanofiber materials were separated by a magnet, washed with deionized water 3 times, and set aside). 2+ The adsorption was repeated for 5 times in total, and the saturated adsorption capacity of each regeneration cycle was tested. The test method of the saturated adsorption capacity was the same as the test method of the saturated adsorption capacity of the dye in the above-mentioned adsorption performance and response performance tests. The experimental data of the saturated adsorption capacity of each regeneration cycle are shown in Table 4.

[0145] Table 4: Saturated adsorption capacity of MB and copper ions of the modified nanofiber materials of Example 1 and Comparative Example 4 (regeneration cycle 5 times)

[0146]

[0147] It can be seen from Table 4 that after five regeneration cycles, the modified nanofiber material in Example 1 of the present invention also has a good adsorption effect, the adsorption capacity is slightly attenuated, and it shows a good recycling performance. The modified nanofiber material in Comparative Example 4 has a poor recycling performance.

[0148] In summary, the present invention modifies nanocellulose by using a specific copper-manganese-iron composite magnetic auxiliary agent to obtain modified nanocellulose, and under the action of an initiator, the modified nanocellulose and a temperature-responsive monomer work together to make the modified nanofiber material have good adsorption properties and magnetic and temperature dual-responsive properties. During separation, the magnetic modified nanofiber material can be separated by a magnetic field, and the adsorbed target pollutants can be eluted by changing the temperature, thereby achieving low-cost recovery and regeneration of the adsorbent, and solving the problem of difficult recovery of traditional water treatment adsorbents after use and the problem of secondary pollution caused by adsorbent regeneration.

[0149] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A modified nanofiber material, characterized in that: The raw materials for its preparation include modified nanocellulose, temperature-responsive monomers, and initiators; The modified nanocellulose is obtained by modifying the nanocellulose with a copper-manganese-iron composite magnetic auxiliary agent.

2. The modified nanofiber material according to claim 1, characterized in that: The copper-manganese-iron composite magnetic auxiliary agent comprises copper chloride, manganese chloride and ferric chloride; the molar ratio of the ferric chloride, copper chloride and manganese chloride is (0.5-1.5):(0.5-1.5):

1.

3. The modified nanofiber material according to claim 1, characterized in that: The mass ratio of the modified nanocellulose to the temperature-responsive monomer is (0.8-12):

1.

4. The modified nanofiber material according to claim 1, characterized in that: The mass ratio of the initiator to the temperature-responsive monomer is 1:(40-120).

5. The modified nanofiber material according to any one of claims 1 to 4, characterized in that: The temperature-responsive monomer includes at least one of N-isopropylacrylamide, polyethylene oxide, and polyvinyl pyrrolidone; and / or the initiator includes at least one of potassium persulfate, ammonium persulfate, and sodium persulfate.

6. The method for preparing the modified nanofiber material according to any one of claims 1 to 5, characterized in that: The following steps are involved: The raw material components are mixed and reacted to obtain the modified nanofiber material.

7. The preparation method according to claim 6, characterized in that: The reaction temperature is 55-85°C; the reaction time is 0.5-2.2h.

8. The preparation method according to claim 6, characterized in that: The preparation method of the modified nanocellulose comprises the following steps: The nanocellulose, copper-manganese-iron composite magnetic auxiliary agent and water are mixed, the pH is adjusted to alkaline, and the mixture is reacted to obtain the modified nanocellulose.

9. The preparation method according to claim 8, characterized in that: The reaction temperature is 150-250° C., the reaction time is 0.5-2.2 h, and the reaction pH is 8-11.

10. Use of the modified nanofiber material according to any one of claims 1 to 5 in wastewater or waste gas treatment.

Citation Information

Patent Citations

  • Preparation method and application of temperature-sensitive hydrogel

    CN109364889A

  • Near-infrared regenerative intelligent fiber-based adsorptive material and preparation method and use thereof

    US11045788B1